Internal and External Mechanisms of Englishization: Changes in Marked and Unmarked Chinese Passive Constructions - Zhang, Liulin; Amoroso, Luke (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The Chinese language is changing, and like other languages, has been becoming more like English. This article focuses on the Englishization (Europeanization) of certain Chinese passive constructions. Previous research indicates that written Chinese has seen an increase in the use of the 被 bèi passive construction (BEIC) and a concomitant decrease in use of the notional passive construction (NPC) over time. This assertion is supported by a corpus-based analysis. An apparent-time research study shows that, in general, younger, more educated participants (those hypothesized to have more exposure to English) are more likely to use BEIC than are older, less educated participants in the sentence continuation task. However, this difference between groups is not captured in the binary forced choice task due to the increased use of BEIC under a conscious condition by the older, less educated participants. This finding sheds light on the psychological mechanism of internalization involved with Englishization.